Arbeitsmarkt 2030 - Die Bedeutung der Zuwanderung für Beschäftigung und Wachstum Prognose 2014 - Vogler-Ludwig, Kurt (W. Bertelsmann Verlag, 2015)
What are the effects of migration into Germany on growth and employment? Can immigrants close the skilled worker gap? Is Germany an immigration country? The study develops an empirically founded profile of changes in the economy and society in Germany until 2030. It identifies skilled worker bottlenecks and offers recommendations for ensuring a sufficient supply of workers. That includes the integration of migrants, an expansion of the adult education system and a long-term, forward-looking family policy on the basis of an improved compatibility of family and work life. The study was commissioned by the Federal Ministry of Labour and Social Affairs (Bundesministerium für Arbeit und Soziales).